Molecular Identification of I-2 Gene, a Fusarium Wilt Resistant Marker in Selected Varieties of Tomato - Mahmood, Tariq; Aziz, Nobia; Ullah, Inam; Azizuddin; M. Abbasi, Fida; Ali, Hamid; Shah, Hussain (Current Trends in OMICS, 2023)
Fusarium wilt is a well-known disease of tomatoes all over the world. The use of resistant varieties is the most efficient approach to control this disease. The current study was carried out to investigate the presence of marker gene(s) resistant to Fusarium wilt in tomato germplasm. This research subsequently sets out which one of the resistant varieties is suitable to be used to contain the disease. Thirteen varieties namely Pusa ruby, Pant bahar, Punjab chhahara, Arka alak, Arak abha, Ratan, CLN-2116-B, CLN-1767-238-2Y, CLSN-2123-A, CLN-1621-E, CLN-1621-T, CLN-1621-L, and CLN-2026-C were screened for the presence of I-2 resistance gene, a marker known to confer resistance to the race 2 of F. oxysporum f. sp. Lycopersici, using PCR-based molecular identification. Two varieties namely Arak abha and Ratan were tested positive for the presence of I-2 against race 2 of the pathogen.